Influencia del aceite de palma aceitera (Elaeis Guineensis, Jacq) en la producción de jabones, cremas y bálsamos. - Monserrate Mayorga, Victor Manuel (2024)
This study focuses on the influence of oil palm oil (Elaeis guineensis, Jacq) in the cosmetics industry, comparing its performance and benefits with other vegetable oils commonly used in the production of soaps, creams and balms. Various analyzes were carried out on the information obtained from scientific sources to establish production efficiency, as well as the physicochemical characteristics, the economic and environmental impact of the use of palm oil in cosmetic products. While the comparison in the energy efficiency of palm oil is greater, reaching 88% compared to 85% of other essential oils, added to this, red palm oil is rich in bioactive compounds such as carotenoids (500-700 ppm) and tocotrienols (600-1200 ppm) which provide antioxidant and vitamin benefits, making palm oil ideal for cosmetic formulations that require stability and specific texture.